2015
DOI: 10.1073/pnas.1519633112
|View full text |Cite
|
Sign up to set email alerts
|

On artifacts in single-molecule force spectroscopy

Abstract: In typical force spectroscopy experiments, a small biomolecule is attached to a soft polymer linker that is pulled with a relatively large bead or cantilever. At constant force, the total extension stochastically changes between two (or more) values, indicating that the biomolecule undergoes transitions between two (or several) conformational states. In this paper, we consider the influence of the dynamics of the linker and mesoscopic pulling device on the force-dependent rate of the conformational transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 41 publications
3
102
0
Order By: Relevance
“…13,15,24 In practice, all these paths are similar, as illustrated by the above comparison between the values of the transition path velocity at the top of the barrier estimated using Eq. (22) and using the theory of dominant transition paths in Ref. 15.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…13,15,24 In practice, all these paths are similar, as illustrated by the above comparison between the values of the transition path velocity at the top of the barrier estimated using Eq. (22) and using the theory of dominant transition paths in Ref. 15.…”
Section: )mentioning
confidence: 99%
“…Our analysis would then still apply to the dynamics of the observed quantity y(t), but recovering the intrinsic properties of x(t) may require explicit consideration of the coupling between the instrument and the molecule of interest, possibly along the lines of Refs. 22 …”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…S5), but D implied by the exponential tail of the distribution decreased about 35% more than did D implied by τ tp . These simulations thus suggest that barrier anharmonicity accounts for up to one-half of the observed discrepancy between the two estimates of D. The rest of the discrepancy presumably arises from contributions from other factors, such as deviations from 1D behavior that distort P TP (t) from expectations, or the mechanical coupling of the hairpins to the linkers and beads, which can alter kinetic properties (24,(52)(53)(54)(55) including transition times (24,55). Such effects are expected to be relatively small, however: previous analysis of some of the same DNA hairpins found that the conditional transition path probability matched expectations for 1D diffusion over the measured landscapes quite well (32), and our measurements are done in a limit where the mechanical coupling artifacts are small (56).…”
Section: Discussionmentioning
confidence: 84%
“…Having attracted recent attention, [48][49][50] such artifacts can be accounted for by introducing an additional degree of freedom describing the instrument itself.…”
mentioning
confidence: 99%